Análisis de los elementos semióticos comunes en las películas: “Cuando me toque a mí”; “Impulso”; “Prometeo Deportado”; “A tus espaldas” y “Pescador”. - Erique Aguirre, Fernando Javier (2022)
The present research focuses on the semiotic analysis of five Ecuadorian films based on the proposals assigned in rhetorical models of visual communication, so that the photography of each of the films shot by different Ecuadorian directors in a period of time that corresponds to the last decade is analyzed. The main objective of this work is governed by the systematization of the meaning of each of the symbolic element’s referents made on the basis of an audiovisual and rhetorical narrative structure that starts from the relationship between the message transmitted, expressed in a visual language and the interpretation of the common semiotic elements that the viewer performs spontaneously. At the same time, the characteristics of each of the films are also included, thus revealing significant elements both for the final analysis and to generate a complement in the cinematographic theme and in visual communication through the description of the representative factors that identify the audience. The study starts from the creation of two observation cards, the first one is distinguished for being a technical card while the second one will allow recording each of the technical aspects of the photography and production of the films. So, it will proceed with the segmentation by scenes of each of the five selected films, then it will be divided by shots to be analyzed with meticulousness to each of them. The research will open a new format of film analysis not only from a technical perspective but also using the science of semiotics to identify representative resources of our society, thus making them more understandable and interesting to existing and future national films.